Medicinal herbs as growth and health promoters in African catfish (Clarias gariepinus, burchell) - Sheikhlar, Atefeh (2012)
In order to investigate the antimicrobial activity of aqueous and methanolicextracts of four plants, Euphorbia hirta(asthma herb),Trigonella foenum-graecum seed (fenugreek),Citrus limonpeel (lemon) and Morus alba foliage (mulberry) on growth performance and prevention of Aeromonas hydrophila in African catfish (Clarias gariepinus),five experiments were carried out. In the first experiment, the effect of aqueous and methanolic extracts of aforementioned plants were investigated against two Gram- negative bacteria, Aeromonas hydrophila and Escherichia coli and two Grampositive bacteria, Streptococcus agalactiae, and Staphylococcus aureusand thephytochemical compounds of the tested herbal extracts were determined.The 2nd study was designed to evaluate the effects of dietary incorporating of these extracts (at different levels) in African catfish (Clarias gariepinus). In this regard, assessing the effect of EHE and MFE supplemented diets on the growth, hematology and histology (kidney and liver) was conducted. The effect of inclusion of EHE in the diet on growth and disease prevention in the catfish was evaluated in the 3rd study. In the 4th study, The effect of inclusion of EHE in the diet on growth and disease prevention in the catfish was investigated. In the 5th study, the effects of dietary mixed-herbal (E. hirta and Morus alba) methanolicextracts(E-ME) on growth, nutrient digestibility, hematological and intestinal indices, antioxidant activity and disease prevention in the catfish were investigated. In the first experiment, the aqueous and methanolic extracts were obtained using distilled water and methanol. To examine antimicrobial characteristics of each extracts against tested bacteria the paper disc diffusion method was used.The experiments were conducted at an Aquatic Animal Health Unit, Faculty of Veterinary Medicine, Universiti Putra Malaysia. Fingerling African catfish (Clarias gariepinus) used in this study, were obtained from a local farm. The fish were weighed and kept in 100-l aquaria with 30 fish per aquarium. The initial weight per fish was around 9.5. Each treatment had three replicates and fish were fed over a period of 60 days (feeding experiment) and 30 days (challenge test).Growth performance, hematological parameters, meat antioxidant activity and cumulative mortality were determined in these studies. The results of first study indicated that based on the inhibition zone, the aqueous extracts of Trigonella foenum-graecumseed (TS) and Citrus limon peel (CP) revealed weak antibacterial activity against the bacteria. However, E. hirta (EH) and M. alba foliage (MF) aqueous extract at a concentration of 100 mg/ml showed moderate and weak activities respectively. The methanolic extracts of all herbs exhibited stronger antimicrobial activities against the tested pathogensas compared to the water extracts. Among the entire methanolic extracts, the EH and MF had the strongest activities, whilethe others exhibited moderate or weak activities. Moreover, the results indicated that A. hydrophila was the most sensitive microorganism tested, with the highest inhibition zone in the presence of the methanolic extracts obtained from EH and MF. The phytochemical screening of the methanol extract of E.hirta (EHE) and methanol extract of M. alba foliage (MFE) showed the presence of secondary metabolites such as phenols, volatile oils, tannins, saponins, steroids, flavonoid, terpenoids and alkaloids. Results of2nd revealed no negative effects of EHE and MFE (at 7 g/Kg DM of diet) in the experimental diets on the fish, while by increasing the level of EHE and MFE to 9 g/Kg,it showed some negative changes in the growth, hematological characteristics and istological assessment. Results of 3rd study showed that growth performance was positively affected by dietary supplements. Mortality rate decreased in fish fed EHE-5 and EHE-7 (5 and 7g/Kg of DM) supplemented diets. Red blood cells, albumin and total protein increased in fish fed with EHE-7 diet compared to other groups. The meat from fish fed with the EHE supplemented diet (EHE-7) was higher for total phenols content and the free radicalscavenging effect (DPPH) than the other dietary groups. Dietary EHE did not change the lipid oxidation (TBARS) of meat. It was shown that storage time had significant effect on meat antioxidative potential. The results of hematological profile after artificial infection with A. hydrophila revealed that RBC, Hb, Ht, total protein, albumin and globulin were better for group offered with EHE-7 diet compared to untreated control, EHE-2 and EHE-5. All the measurements in the A.hydrophila infected fish which fed in the EHE at 7 g/kg DM (EHE-7) showed similar values compared with the control and the treatment groups which received antibiotic. The fish fed EHE-5 showed lower cumulative mortality than fish fed with EHE-2 and untreated control, while the group fed with EHE-7 had the lowest cumulative mortality among others.The results of the 4th study showed that inclusion of M.alba foliage extract (MFE) did not improve the growth performance. The values of RBC, Hb and serum albumin and total protein were all higher for the treatment MFE-5 and MFE-7 than other treatments.The meat from fish fed MFE-5 and MFE-7 had significantly greater total phenols content than other dietary groups. The free radicalscavenging (DPPH) activity of meatfrom fish fed MFE was significantly improved.The DPPH-scavenging effect of the MFE -7diet was higher than that of thecontrol, MFE-2 and MFE-5 diets. Dietary MFE (at any level) did not affect the lipid oxidation (TBARS) of meat. It was shown that storage time had significant effect on meat antioxidative potential. In the challenge test, all the measurements (RBC, Hb, Ht, total protein, albumin and globulin) in the A. hydrophila infected fish fed with the MFE-5 and MFE-7 diets showed similar values compared with the control treatments (healthy control and antibiotic treated control).Cumulative mortality decreased by inclusion of the extract in the diet and the fish fed MFE-7 had the lowest cumulative mortality over the period of infection. Results of the 5th study showed that growth performance improved in fish fed EHE supplemented diet compared to other groups. The values of RBC counts, Hb and serum albumin and total protein were all higher for the treatments with EHE, MFE and EME than for the control treatment.The meat from fish fed with different extracts (EHE,MFE and E-ME diets) had significantly greater total phenols content as well as free radical-scavenging (DPPH) effect than the meat of fish fed with the control diet. The lipid oxidation (TBARS) values of fish fed EHE, MFE and E-ME diets did not increase during storage, while that of control group increased. In the present experiment,determination of apparent digestibility showed that the digestibility for dry matter and crude protein were higher for the fish fed EHE diet than the MFE and control diets. Post infection hematological profile revealed that fish fed with EHE, MFE and E-ME diets had RBC, Hb, Ht, total protein, albumin and globulin values comparable with healthy and antibiotic treated controls. Furthermore, the cumulative mortality in the fish that received EHE, MFE and E-ME diets were much lower than untreated groups. Histologicalassessment of intestine in this experiment showed no abnormalities. In conclusion, these studies suggested that the methanolic extract of E. hirta and M. alba foliage were found to be effective in growth improvement and bacterial disease prevention in African catfish. On the other hand, the benefits obtained from the inclusion of mixed-herbal extracts were not synergistic.